Analisis Standar Isi Dalam Perspektif Manajemen Mutu Pendidikan - Nurul Kholilah (THE JOER: Journal Of Education Research, 2023)
Content standards are minimum criteria that cover the scope of material to achieve graduate competence in certain paths, levels and types of education. This study aims to determine: 1) Content standards in quality management of education at MTs Negeri 2 Pasuruan. 2) Analysis of content standards in the perspective of education quality management at MTs Negeri 2 Pasuruan This research uses qualitative research, with a case study research design at MTs Negeri 2 Pasuruan. Data was collected by interview, observation, and documentation methods. Data analysis techniques through data collection, data reduction, data presentation and drawing conclusions. Data validity technique, using source and theory triangulation. Based on the research data obtained: Analysis of content standards in the perspective of education quality management at MTs Negeri 2 Pasuruan is carried out by matching data between ideal conditions and existing real conditions starting from planning, implementation, monitoring and supervision, curriculum evaluation carried out to the maximum and responsibility by all stakeholders to improve the quality of education at MTs Negeri 2 Pasuruan.